Driftwood Bay [large type] - Hannon, Irene (Hannon, Irene. Hope Harbor ;, 2019)
"Jeannette Mason swore off relationships of any kind when she moved to Hope Harbor to start a new life--but a single dad with a grieving little girl and an unruly pup may test that resolve"--